2015
DOI: 10.1021/acs.accounts.5b00102
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease: A Heme–Aβ Perspective

Abstract: CONSPECTUS: Redox active iron is utilized in biology for various electron transfer and catalytic reactions essential for life, yet this same chemistry mediates the formation of partially reduced oxygen species (PROS). Oxidative stress derived from the iron accumulated in the amyloid plaques originating from amyloid β (Aβ) peptides and neurofibrillary tangles derived from hyperphosphorylated tau proteins has been implicated in the pathogenesis of Alzheimer's disease (AD). Altered heme homeostasis leading to dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 76 publications
3
77
0
Order By: Relevance
“…[51][52][53] Moreover, heme binding to amyloid-β peptides and the altered heme homeostasis in Alzheimer's disease have also been demonstrated. 50,54 There are serious lacuna, however, in understanding the chemical nature of hemin-peptide and bile pigment-peptide interactions, which instigated us to study how these compounds affect the secondary structure of intrinsically disordered model peptides. Our work supplies direct spectroscopic evidences on the complex, sequence-dependent, significantly different structure modifying ability of hemin and its natural derivatives mediated by hydrophobic (Trp-porphyrin) and most likely ionic (Lys/Arg-propionate) forces.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] Moreover, heme binding to amyloid-β peptides and the altered heme homeostasis in Alzheimer's disease have also been demonstrated. 50,54 There are serious lacuna, however, in understanding the chemical nature of hemin-peptide and bile pigment-peptide interactions, which instigated us to study how these compounds affect the secondary structure of intrinsically disordered model peptides. Our work supplies direct spectroscopic evidences on the complex, sequence-dependent, significantly different structure modifying ability of hemin and its natural derivatives mediated by hydrophobic (Trp-porphyrin) and most likely ionic (Lys/Arg-propionate) forces.…”
Section: Discussionmentioning
confidence: 99%
“…One of the residues of H13 and H14 in Aβ has been suggested as a heme‐binding‐ligand . Peroxidase reactions promoted from Aβ‐heme complexes are facilitated by the presence of N‐terminal residues R5 and Y10, residues that are absent in the Aβ peptide naturally expressed in rodents . Copper ion interaction is not compromised when simultaneously present with heme molecules .…”
Section: Metal Ion Interactions Of the Aβ Peptidementioning
confidence: 99%
“…[71] Peroxidase reactions promoted from Ab-heme complexes are facilitated by the presence of N-terminal residues R5 and Y10, residues that are absent in the Ab peptide naturally expressed in rodents. [72] Copper ion interaction is not compromised when simultaneously present with heme molecules. [73] Ab fibril formation is inhibited in the presence of heme, and mutational studies indicate contributions from both iron and porphyrin interactions.…”
Section: Ironmentioning
confidence: 99%
“…The interaction of hemin and other water-soluble phthalocyanines, corroles, and porphyrins with Ab has been noted. [29][30][31][32] We thus envisaged that coupling the Ab-recognition properties of metalloporphyrins with the biological activity of metallotexaphyrins would allow for MRI recognition of Ab species with attendant utility as a potential metalloantioxidant therapeutic ( Figure 2). As detailed further below, we have found that metallotexaphyrins, in particular MMn, interact with amyloid constructs, as inferred from ultraviolet-visible (UV-vis), fluorescence, and circular dichroism (CD) spectroscopies, as well as MRI studies.…”
Section: Introductionmentioning
confidence: 99%